2011
DOI: 10.1080/14647893.2011.575220
|View full text |Cite
|
Sign up to set email alerts
|

The empathy and the structuring sharing modes of movement sequences in the improvisation of contemporary dance

Abstract: Dance, an activity endowed with intentional expressivity and intrinsic affectivity, has been the target of neuroscientific research since the last decade of the 20th century. We can make several inferences about the cognitive and motor aspects in dance based on this research. The main goal of the present study is to raise questions about how communication takes place among dancers during dance improvisation. This work is based on a systematic review of the literature. In this paper we approach the cognition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…Selforganisation is something that show up better in the limit between order and chaos; therefore, a task can follow a mechanical order without any other answer possibility but it does not necessarily have to follow an order, and the other way round. The sensorial perception of the performance depends on how the body feels and works, what it desires, does and suffers (Hristovski et al, 2011;Schuterman, 1999;Ribeiro and Fonseca, 2011).…”
Section: Recreation Of One's History (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Selforganisation is something that show up better in the limit between order and chaos; therefore, a task can follow a mechanical order without any other answer possibility but it does not necessarily have to follow an order, and the other way round. The sensorial perception of the performance depends on how the body feels and works, what it desires, does and suffers (Hristovski et al, 2011;Schuterman, 1999;Ribeiro and Fonseca, 2011).…”
Section: Recreation Of One's History (1)mentioning
confidence: 99%
“…As inspiration is autocatalysed by the artist's response to the excitement of creativity, the non-linearity of the situation increases (Kelso, 1997;Zausner, 1996). In the case of dance, improvisation requires the cognition and relationship with one's partner and space (Ribeiro and Fonseca, 2011). The body's response may be conditioned by elements such as experiences, values, tastes, desires and technique (Blom and Chaplin, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they must rely on other senses such as hearing, touch, and kinesthesia, in order to develop social connections with others, while having little to no knowledge of 'who' that person is, nor what one's socially prescribed relationship with that other person is (Gallese, 2003;Hertenstein, Keltner, App, Bulleit, & Jaskolka, 2006;Ribeiro & Fonseca, 2011;Verstegen 2005, p.22). Sensing another's presence can guide one to move closer or further; feeling another's touch can cause one's body to react with new movement.…”
Section: Reflectionsmentioning
confidence: 99%
“…Due to the mostly non-verbal character of the practice, it allows greater focus on embodied means of communication. Ribeiro and Fonseca (2011) suggested that collaboration and communication between improvisers are mediated by 'kinaesthetic empathy.' This they define as the ability to understand others' actions and emotions through embodied feelings, which tend to match others' states.…”
Section: Introductionmentioning
confidence: 99%